2007
DOI: 10.3103/s0096392507010014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental associations of cyanobacteria and actinomycetes

Abstract: Актиномицеты выделяли из накопительной культуры О. terebriformis и предварительно растер тых апогеотропных корней саговников методом по сева и рассыпки (соответственно) на агаризован-ную питательную среду. Выделение и культивиро вание стрептомицетов проводили на среде Гаузе-1 (Гаузе и др., 1983).Поддержание монокультуры цианобактерий про водили: О. terebriformis -на среде Заварзина (Орле анский, Герасименко, 1982); A. variabilis -на среде BG-11 (Stanier et al., 1971). Культивирование циа нобактерий проводили … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Morphological and ultrastructural peculiarities allowed identifying the planctomycetes, prosthecobacteria belonging to the genus Caulobacter and actinomycetes among non-phototrophic epibiotic bacteria. The actinomycetes were identified as the representatives of the genus Streptomyces by means of isolation in the enrichment culture and phagotyping (Omarova et al , 2008). Certain epibiotic forms of cyanobacteria and other prokaryotes display defective rigidity of the cell wall, and partial or complete reduction of the cell wall (forms with defective cell wall—FDCW) (Gorelova et al , 2009b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological and ultrastructural peculiarities allowed identifying the planctomycetes, prosthecobacteria belonging to the genus Caulobacter and actinomycetes among non-phototrophic epibiotic bacteria. The actinomycetes were identified as the representatives of the genus Streptomyces by means of isolation in the enrichment culture and phagotyping (Omarova et al , 2008). Certain epibiotic forms of cyanobacteria and other prokaryotes display defective rigidity of the cell wall, and partial or complete reduction of the cell wall (forms with defective cell wall—FDCW) (Gorelova et al , 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…Morphological and ultrastructural characters allowed identifying planctomycetes, prosthecobacteria, actinomycetes and cyanobacteria as prokaryotes associated with hydroid. After sterilization we managed to isolate unicellular microalgae and different bacteria (including those capable of nitrogen fixation) from the tissues of the hydroid colony (Omarova et al , 2008; Gorelova et al , 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Also, other studies have shown the stimulation of Oscillatoria terebriformis growth in the associated culture with the streptomyces strain. In addition, increased nitrogen fixation by Anabaena variabilis and higher photosynthetic activity of O. terebriformis in streptomyces-associated culture was recorded [ 62 ]. Michel et al [ 63 ] showed that some algae and actinobacteria are closely related in their evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The association of bacteria with a cyanobacterial host is quite diverse and encompasses all phyla including Firmicutes, Actinobacteria, and γ-proteobacteria [14]. These assemblages constitute highly specific symbiotic relationships.…”
Section: Introductionmentioning
confidence: 99%